Ultrastructural and nuclear antigen preservation after high-pressure freezing/freeze-substitution and low-temperature LR White embedding of HeLa cells - Strádalová, Vendula; Gaplovská-Kyselá, Katarína; Hozák, Pavel (Histochemistry and cell biology, 2008)
A protocol for high-pressure freezing and LR White embedding of mammalian cells suitable for fine ultrastructural studies in combination with immunogold labelling is presented. HeLa S3 cells enclosed in low-temperature gelling agarose were high-pressure frozen, freeze-substituted in acetone, and embedded in LR White at 0 degrees C. The morphology of such cells and the preservation of nuclear antigens were excellent in comparison with chemically fixed cells embedded in the same resin. The immunolabelling signal for different nuclear antigens was 4-to-13 times higher in high-pressure frozen than in chemically fixed cells. We conclude that one can successfully use high-pressure freezing/freeze-substitution and LR White embedding as an alternative of Lowicryl resins.
Keywords: mrazová substituce; Acrylic Resins; Cell Nucleus; Cryopreservation; akrylové pryskyřice; antigeny jaderné; imunohistochemie; buněčné jádro; HeLa buňky; Antigens, Nuclear; zalévání tkání plastickou hmotou; lidé; Microscopy, Electron, Transmission; Immunohistochemistry; HeLa Cells; Plastic Embedding; Humans; Freeze Substitution; Pressure; tlak; kryoprezervace; transmisní elektronová mikroskopie